Multiple Regulatory Mechanisms Control the Production of CmrRST, an Atypical Signal Transduction System in Clostridioides difficile - Garrett, Elizabeth M.; Mehra, Anchal; Sekulovic, Ognjen; Tamayo, Rita (mBio, 2021)
Clostridioides difficile is a leading cause of hospital-acquired intestinal infections in the United States. The CmrRST signal transduction system controls numerous physiological traits and processes in C. difficile , including cell and colony morphology, motility, biofilm formation, and virulence. Clostridioides difficile , an intestinal pathogen and leading cause of nosocomial infection, exhibits extensive phenotypic heterogeneity through phase variation. The signal transduction system CmrRST, which encodes two response regulators (CmrR and CmrT) and a sensor kinase (CmrS), impacts C. difficile cell and colony morphology, surface and swimming motility, biofilm formation, and virulence in an animal model. CmrRST is subject to phase variation through site-specific recombination and reversible inversion of the “ cmr switch,” and expression of cmrRST is also regulated by cyclic diguanylate (c-di-GMP) through a riboswitch. The goal of this study was to determine how the cmr switch and c-di-GMP work together to regulate cmrRST expression. We generated “phase-locked” strains by mutating key residues in the right inverted repeat flanking the cmr switch. Phenotypic characterization of these phase-locked cmr -ON and -OFF strains demonstrates that they cannot switch between rough and smooth colony morphologies, respectively, or other CmrRST-associated phenotypes. Manipulation of c-di-GMP levels in these mutants showed that c-di-GMP promotes cmrRST expression and associated phenotypes independently of cmr switch orientation. We identified multiple promoters controlling cmrRST transcription, including one within the ON orientation of the cmr switch and another that is positively autoregulated by CmrR. Overall, this work reveals a complex regulatory network that governs cmrRST expression and a unique intersection of phase variation and c-di-GMP signaling. These findings suggest that multiple environmental signals impact the production of this signaling transduction system. IMPORTANCE Clostridioides difficile is a leading cause of hospital-acquired intestinal infections in the United States. The CmrRST signal transduction system controls numerous physiological traits and processes in C. difficile , including cell and colony morphology, motility, biofilm formation, and virulence. Here, we define the complex, multilevel regulation of cmrRST expression, including stochastic control through phase variation, modulation by the second messenger c-di-GMP, and positive autoregulation by CmrR. The results of this study suggest that multiple, distinct environmental stimuli and selective pressures must be integrated to appropriately control cmrRST expression.